1978
DOI: 10.1172/jci108989
|View full text |Cite
|
Sign up to set email alerts
|

Coordinacy of lysosomal enzyme excretion in human urine.

Abstract: A B S T R A C T Assay conditions have been developed for the determination of urinary 8-glucuronidase, ,8-galactosidase, a-galactosidase, and, -hexosaminidase using fluorometric substrates. The assay conditions for ,8-glucuronidase overcome interference by both low and high molecular weight inhibitors, a problem that has confused earlier studies of enzyme excretion.The fouir lysosomal enzymes are excreted coordinately; although their absolute levels (in units per milligram of creatinine) vary during the day an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

1978
1978
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(36 citation statements)
references
References 40 publications
2
34
0
Order By: Relevance
“…Exocytosis seems the most probable explanation (1). This phenomenon has been described in other mammalian cells (24) and has recently been proposed to explain the excretion oflysosomal hydrolases in human urine (25). Furthermore, there are morphologic studies indicating exocytic discharge of lysosomal contents in bile canaliculi (2-4, 26, 27).…”
Section: Discussionmentioning
confidence: 61%
“…Exocytosis seems the most probable explanation (1). This phenomenon has been described in other mammalian cells (24) and has recently been proposed to explain the excretion oflysosomal hydrolases in human urine (25). Furthermore, there are morphologic studies indicating exocytic discharge of lysosomal contents in bile canaliculi (2-4, 26, 27).…”
Section: Discussionmentioning
confidence: 61%
“…a-Glucosidase activity was measured in the medium and in the cell extract Activity added to medium Mannose Activity in 6-phosphate cells after in medium 24h source amount mU mM mU/mg protein Values are means of duplicate measurements in two separate preparations. In a parallel incubation a known amount of pure mannose 6-phosphate was subjected to the same procedure as the samples; the mannose 6-phosphate content decreased by 20 % [23] have found that several lysosomal enzymes are secreted into the urine in a coordinated fashion. The secretion of lysosomal enzymes is unrelated to that of the cytosolic enzyme lactate dehydrogenase, suggesting that the lysosomal enzymes found in the urine are not derived from exfoliated cells but are actively secreted.…”
Section: Purifcation Of Lysosomal A-glucosidase From Human Urinementioning
confidence: 99%
“…Due to this location of the B isoform (U-NAG-B), it is massively released in the tubular lumen only in the case of cytolytic tubular lesion. Its presence in the urine correlates with the cell lysis and is marked as lesion enzymuria [8,9]. NAG could also be detected in the circulation.…”
Section: Renal Markers For Estimation Of Renal Dysfunctionmentioning
confidence: 93%
“…Of all the urinary enzymes, U-NAG (urinary) has been extensively examined. It belongs to the class of hydrolases present in a large amount in the lysosomes in the proximal tubular cells [8]. In the human body and biological fluids there are two major enzyme forms: A (Acid) and B (Basic) [3][4][5].…”
Section: Renal Markers For Estimation Of Renal Dysfunctionmentioning
confidence: 99%